How to be a writer. Between the lines. Nathan Englander / CreativeLive. - Corrigan, Kelly, 1967-; Englander, Nathan (Academic Video Online, 2017)
Nathan Englander is the author of the collection What We Talk About When We Talk About Anne Frank, as well as the internationally bestselling story collection For the Relief of Unbearable Urges, and the novel The Ministry of Special Cases (all published by Knopf/Vintage). He was the 2012 recipient of the Frank O'Connor International Short Story Award and a finalist for the 2013 Pulitzer Prize for What We Talk About. His short fiction and essays have appeared in The New Yorker, The New York Times, The Atlantic Monthly, and The Washington Post, as well as The O. Henry Prize Stories and numerous editions of The Best American Short Stories. Translated into twenty languages, Englander was selected as one of "20 Writers for the 21st Century" by The New Yorker, received a Guggenheim Fellowship, a PEN/Malamud Award, the Bard Fiction Prize, and the Sue Kaufman Prize from the American Academy of Arts & Letters. He's been a fellow at the Dorothy & Lewis B. Cullman Center for Scholars and Writers at the New York Public Library, and at The American Academy of Berlin. He is currently the Distinguished Writer-in-Residence at New York University. In 2012, along with the publication of his new collection, Englander's play The Twenty-Seventh Man premiered at The Public Theater, and his translation New American Haggadah (edited by Jonathan Safran Foer) was published by Little Brown. He also co-translated Etgar Keret's Suddenly A Knock at the Door, published by FSG. He lives in Brooklyn, New York and Madison, Wisconsin.